Regional locus coeruleus degeneration is uncoupled from noradrenergic terminal loss in Parkinson’s disease - Doppler, Christopher E J; Kinnerup, Martin B; Brune, Corinna; Farrher, Ezequiel; Betts, Matthew; Fedorova, Tatyana D; Schaldemose, Jeppe L; Knudsen, Karoline; Ismail, Rola; Seger, Aline D; Hansen, Allan K; Stær, Kristian; et al. (Brain (London, England : 1878), 2021)
Previous studies have reported substantial involvement of the noradrenergic system in Parkinson’s disease. Neuromelanin-sensitive MRI sequences and PET tracers have become available to visualize the cell bodies in the locus coeruleus and the density of noradrenergic terminal transporters. Combining these methods, we investigated the relationship of neurodegeneration in these distinct compartments in Parkinson’s disease. We examined 93 subjects (40 healthy controls and 53 Parkinson’s disease patients) with neuromelanin-sensitive turbo spin-echo MRI and calculated locus coeruleus-to-pons signal contrasts. Voxels with the highest intensities were extracted from published locus coeruleus coordinates transformed to individual MRI. To also investigate a potential spatial pattern of locus coeruleus degeneration, we extracted the highest signal intensities from the rostral, middle, and caudal third of the locus coeruleus. Additionally, a study-specific probabilistic map of the locus coeruleus was created and used to extract mean MRI contrast from the entire locus coeruleus and each rostro-caudal subdivision. Locus coeruleus volumes were measured using manual segmentations. A subset of 73 subjects had 11C-MeNER PET to determine noradrenaline transporter density, and distribution volume ratios of noradrenaline transporter-rich regions were computed. Patients with Parkinson’s disease showed reduced locus coeruleus MRI contrast independently of the selected method (voxel approaches: P < 0.0001, P < 0.001; probabilistic map: P < 0.05), specifically on the clinically-defined most affected side (P < 0.05), and reduced locus coeruleus volume (P < 0.0001). Reduced MRI contrast was confined to the middle and caudal locus coeruleus (voxel approach, rostral: P = 0.48, middle: P < 0.0001, and caudal: P < 0.05; probabilistic map, rostral: P = 0.90, middle: P < 0.01, and caudal: P < 0.05). The noradrenaline transporter density was lower in patients with Parkinson’s diseasein all examined regions (group effect P < 0.0001). No significant correlation was observed between locus coeruleus MRI contrast and noradrenaline transporter density. In contrast, the individual ratios of noradrenaline transporter density and locus coeruleus MRI contrast were lower in Parkinson’s disease patients in all examined regions (group effect P < 0.001). Our multimodal imaging approach revealed pronounced noradrenergic terminal loss relative to cellular locus coeruleus degeneration in Parkinson’s disease; the latter followed a distinct spatial pattern with the middle-caudal portion being more affected than the rostral part. The data shed first light on the interaction between the axonal and cell body compartments and their differential susceptibility to neurodegeneration in Parkinson’s disease, which may eventually direct research towards potential novel treatment approaches.